Tracheal Extubation Under Deep Anesthesia Using Transnasal Humidified Rapid Insufflation Ventilatory Exchange vs. Awake Extubation: An Open-Labeled Randomized Controlled Trial - Qiu, Jin; Xie, Mian; Chen, Jie; Chen, Bing; Chen, Yuanjing; Zhu, Xiwen; Lin, Hui; Zhu, Tao; Duan, Guangyou; Huang, He (Frontiers in Medicine, 2022)
Background: Tracheal extubation can be associated with several complications, including hypoxia, agitation, and adverse haemodynamic effects. We hypothesize that the use of transnasal humidified rapid insufflation ventilator exchange (THRIVE) immediately after extubation under deep anaesthesia reduces the incidence of these adverse events. Methods: One hundred patients who underwent elective abdominal surgery under general anaesthesia were randomly assigned to undergo tracheal extubation under deep anaesthesia employing THRIVE (THRIVE group) or awake extubation (CONTROL group). The primary outcome was the incidence of experiencing hypoxia (SpO2 <90%) at any time during emergence from anaesthesia. Secondary outcomes included variations in heart rate and blood pressure, comfort level, bucking, and agitation. Results: The THRIVE group showed a lower incidence of hypoxia than the CONTROL group (12% vs. 54%, OR = 0.22 [95% CI, 0.10–0.49], P <0.001). Less patients in the THRIVE group experienced a 20% (or more) increase in mean arterial pressure (4% vs. 26%, OR = 0.15 [95% CI, 0.04–0.65], P = 0.002). THRIVE patients did not suffer from agitation or bucking, while in the CONTROL group agitation and bucking occurred in 22% and 58% of the patients, respectively. Additionally, the THRIVE group showed a lower incidence of uncomfortable experience than the CONTROL group (8% vs. 36%, OR = 0.22 [95% CI, 0.08–0.61], P = 0.001). Conclusion: Tracheal extubation under deep anaesthesia using THRIVE decreases the incidence of hypoxia and adverse haemodynamic events and increases patient satisfaction. Extubation under deep anaesthesia using THRIVE might be an alternative strategy in selected patient populations.